Phenotypic variation of basic wood density in Pinus ponderosa plus trees = Variación fenotípica de la densidad básica de la madera de árboles plus de Pinus ponderosa - Martinez Meier, Alejandro; Gallo, Leonardo Ariel; Pastorino, Mario Juan; Mondino, Victor Alejandro; Rozenberg, Philippe (Facultad de Ciencias Forestales y Recursos Naturales, Universidad Austral de Chile, 2019)
Phenotypic selection generally reduces the variability of both the selected trait and other associated characteristics. Some species show a negative strong relationship between growth traits and wood density. In the present study, basic wood density was assessed in a group of 23 control trees and 25 Pinus ponderosa plus trees, selected for growth and form traits in the Argentine Patagonia region. Trees were sampled in four different sites from the environmental and silvicultural point of view. We aim to study if the phenotypic variation in wood density is somehow influenced by the selection for productivity and form. The average wood density of plus trees was 0.37 g cm-3, ranging from 0.29 to 0.46 g cm-3. These values were not significantly different to control trees and were similar to those previously found in P. ponderosa plantations growing in the region. Wood density of the improved population, represented by plus trees did not differ from that of base population from which plus trees were selected. Significant differences were found in wood basic density among sites and age-classes. The phenotypic variation of the increment of wood density from pith to bark and among trees was different from zero. Not significant association was found between wood basic density and growth and form traits, except for stem straightness. It would be possible to identify high wood density trees at half of the rotation age.